Triggering CD40 on endothelial cells contributes to tumor growth - Chiodoni, Claudia; Iezzi, Manuela; Guiducci, Cristiana; Sangaletti, Sabina; Alessandrini, Isabella; Ratti, Chiara; Tiboni, Francesca; Musiani, Piero; Granger, D. Neil; Colombo, Mario P. (The Journal of experimental medicine, 2006)
Inflammatory cells can either promote or inhibit tumor growth. Here we studied whether CD40, a key molecule for adaptive immune response, has any role in mammary carcinogenesis of BALB/NeuT transgenic tumor-prone mice. We transferred the HER2/neu oncogene into CD40-null background to obtain the CD40-KO/NeuT strain. CD40-KO/NeuT mice showed delayed tumor onset and reduced tumor multiplicity. BM (BM) transplantation experiments excluded a role of BM-derived cells in the reduced tumorigenicity associated with CD40 deficiency. Rather, CD40 expressed by endothelial cells (ECs) takes part to the angiogenic process. Accordingly, large vessels, well organized around the tumor lobular structures, characterize BALB/NeuT tumors, whereas tiny numerous vessels with scarce extracellular matrix are dispersed in the parenchyma of poorly organized CD40-KO/NeuT tumors. Activated platelets, which may interact with and activate ECs, are a possible source of CD40L. Their localization within tumor vessels prompted the idea of treating BALB/NeuT and CD40-KO/NeuT mice chronically with the anti-platelet drug clopidogrel, known to inhibit platelet CD40L expression. Treatment of BALB/NeuT mice reduced tumor growth to a level similar to CD40-deficient mice, whereas CD40-KO/NeuT mice treated or not showed the same attenuated tumor outgrowth, indicating that activated platelets are the likely source of CD40L in this model. Collectively, these data point to a participation of CD40/CD40L in the angiogenic processes associated with mammary carcinogenesis of BALB/NeuT mice.